Improving Writing Skills of Santri Through English Training Program at Pondok Pesantren - Rozi, Fahrur; Ikhsananto, Aan; Nazira, Ayesha Shifa; Sari, Septiani Kartika; Oktafiani, Elisa (Universitas Negeri Semarang, 2024)
There are four aspects of English skills: reading skills, writing skills, listening skills, and speaking skills. Writing skills are often also called the art of writing because strategies must be made to get a good response from the readers. This community service aims to assist santri at Pondok Pesantren Putra Putri as Salafy Al Asror Patemon Gunungpati Semarang to improve their writing skills to prepare for employment through English Language Training. It is the right solution to help them learn how to write application letters, prepare for interviews, and develop strategies for answering interview questions in English. This training is accompanied by experienced English and Economics lecturers who create a positive and supportive environment and increase consistency in sharpening the santri' skills. This community service is implemented offline (outside the network) at Pondok Pesantren Putra Putri as Salafy Al Asror Patemon Gunungpati Semarang for one day. Santri can write application letter and have good interview skill in English. Then, the community service results a video and other documents. The expected output targets are publishing articles in journals and mass media publications.